The BAP Responses to the Flowering and Production on variety of Red Onions - Fatiani Manik; Endah Retno Palupi; Mohamad Rahmad Suhartanto (Department of Crop Science, Faculty of Agriculture, Andalas University, 2019)
The use of quality seeds can increase the production of garlic. One indicator of increased yield can be seen from the size of cloves. The research aimed to know the growth and production of garlic from clove size and different seeds storage method. The experiment was conducted at Experimental farm Berastagi that began February-June 2018. The experiments was arranged in Randomized Complete Block Design with two factors. The first factor is the size of cloves, namely: 2.3 g / clove, 1.4 g / clove, 0.7 g / clove and the second factor is the storage method of separation of tubers and separation of cloves.. The observed variables include plant height, leaf number, leaf length, stem diameter, tuber weight, tuber diameter, number of cloves, and ability to grow. The results showed that storage method had significant effect on percentage of germination seed. Clove weight and storage method not significant effect on plant height, leaf number, leaf length, neck diamter, tuber weight, tuber diameter and number of cloves. Interaction occurs between treatments the neck diameter of garlic